P039 The role of α4β7+CLA+ 'dual tropic' T cells in inflammatory bowel disease. (21st January 2022) - Gordon, H; Rodger, B; Hornsby, E; McGuire, J; Kok, K B; Lindsay, J O; Stagg, A J
Abstract: Background: Upon activation, T cells upregulate cell-surface molecules that enable entry into peripheral tissues. Retinoic acid (RA) produced by gut DC induces integrin α4β7 required for gut homing and represses CLA which facilitates skin entry; hence, these markers are usually reciprocally expressed. We aimed to identify the mechanisms enabling dual tropism, define the properties of α4β7+CLA+ T cells and compare blood and intestinal α4β7+CLA+ T cells in health and IBD. Methods: Using flow cytometry, expression of α4β7 and CLA was assessed on (i) ex vivo human T cells from blood and intestinal tissue and; (ii) naïve CD4 T cells stimulated in vitro with antibodies (anti-CD3/28/2), or allogeneic DCs. The role of RA signalling and p38MAPK in CLA expression were investigated with respective antagonists Ro41-5253 and SB203580. Transwell studies were used to investigate whether DC-T cell direct contact was required for CLA expression. Single cell RNA sequencing (scRNAseq) of in vitro activated T cells was undertaken, with feature barcode antibody labelling of β7 and CLA. Differential gene expression and pathway analysis was undertaken. Results: DC-activated T cells contained both α4β7+ and CLA+ cells and included a dual tropic population co-expressing both markers. In contrast, antibody-activated T cells expressed α4β7 but did not express CLA unless RA receptor alpha (RARa) signalling was also inhibited. The DC-derived signals that allowed CLA expression were partially dependent on p38MAPK and required DC-T cell contact for optimal activity. A high frequency of dual tropic T cells produced IFNg or TNFa. ScRNAseq identified 270 genes differentially expressed (fold change <-2 or >+2, FDR<0.01) between α4β7+CLA+ and α4β7+CLA- T populations generated by DC stimulation. Expression of FUT7, a fucosyltransferase implicated in generation of the CLA moiety, was increased in the α4β7+CLA+ population and overall 27 pathways were significantly enriched (p<0.05) in this population, including intestinal immune networks and IBD. Ex vivo, CD4+ and CD8+ dual tropic T cells were found in peripheral blood and intestinal tissue. CD4+ dual tropic T cells were significantly increased in the colon of patients with IBD (p=0.03). Conclusion: DC-derived signals acting via p38MAPK generate pro-inflammatory dual tropic T cells even in the presence of active RA signalling. CLA expression may act as an additional ligand in gut trafficking by binding to selectins on the inflamed vascular endothelium and has a potential role in both gut and skin inflammation in IBD.